IMPACT OF HIGHER WORK MOTIVATION TOWARDS IMPROVEMENT OF EMPLOYEE PERFORMANCE - Oktafien, Shinta; Budi Santoso, Anton (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to find out how much influence work motivation has on employee performance in the West Java Province Human Resources Development Agency. As for the population in this study, it was all employees who worked at the Human Resources Development Agency of West Java Province, totaling 122 people with a total sample of 93 respondents taken. Meanwhile, the research method used in this study is a survey research method with data processing and analysis techniques in the form of simple regression analysis. Based on the results of the study, it is known that work motivation has a significant effect on employee performance in the West Java Province Human Resources Development Agency. This shows that the more motivated the employee is at work, the better the work that is shown by the employee.